Analysis on the ecological impact of the Xiaolangdi Reservoir on the Yellow River Delta wetland and coastal areas - Shang, Wenxiu; Yan, Dengming; Peng, Shaoming; Wang, Yu; Ge, Lei; Shang, Yi (Frontiers in Earth Science, 2022)
An environmental water supplement through reservoir regulation is an important way to restore the deltaic coastal wetland. In order to quantify the impact of the reservoir on the deltaic coastal wetland ecosystem, this article proposes a quantitative analysis method for the ecological impact and contribution rate of the reservoir, which compares the ecological status in two scenarios with the presence or absence of the reservoir during the assessment period, and reveals the reservoir’s impact on and contribution rate to the ecological status and environmental water supplement conditions. The results show that during 2000–2019, through the regulation of the Xiaolangdi Reservoir, the average annual drying up days at the Lijin section reduced by 81.15 days, the average annual assurance rate of ecological base flow at the Lijin section increased by 20.60%, and the volume of water flowing into the sea from April to June increased by 2.37 billion m³. During 2008–2015, the Xiaolangdi Reservoir increased the environmental water supplement of the Yellow River Delta by 19.95 million m³. Compared with the flow and water withdrawal during 1980–1999, the natural flow of the Yellow River decreased by 10.59% and the measured flow in the lower reaches decreased by 22.15%, and the water withdrawal in the lower reaches increased by 0.32 billion m³ during 2000–2019, which is detrimental to provide environmental water to the Yellow River Delta wetland and coastal areas. The Xiaolangdi Reservoir reversed the adverse effects of flow and water withdrawal and ensured the continuous ecological improvement in the Yellow River Delta and coastal areas, providing the respective contribution rate of 187.85%, 137.24%, and 125.83% to the prevention of drying up at the Lijin section, the increase in the assurance rate of ecological base flow at the Lijin section, and the increase in the volume of water flowing into the sea in the critical period.